Participación Ciudadana en la Contratación de Infraestructura Pública: Debilidad de la Transparencia Panameña - Manuel Gerardo González Pinzón; Danysabel María Caballero Miranda (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
Introduction: Early transparency and civic engagement are politically evaluated by legal professionals. Objective: To determine the perception of transparency and the efficacy of the legal framework in public infrastructure procurement in Panama. Methodology: An exploratory sequential mixed-methods design was applied. This approach combined an initial qualitative immersion through open-ended interviews with eight experts, followed by a structured survey administered to forty attorneys. Quantitative data were processed using descriptive statistics, while open-ended responses were analyzed via manually validated thematic coding. Results: The main findings reveal a critical perception: corruption was identified by 75% of respondents, cost overruns by 86%, favoritism by 88%, low civic engagement by 84%, deficiencies in civic education by 92%, and a lack of certainty of punishment by 90%. Conclusions: It is concluded that, despite a formally robust regulatory framework, its practical application is perceived as deficient.